Transition for Adolescents with Autism Spectrum Disorder: South African Parent and Professional Perspectives - Meiring, Meagan; Seabi, Joseph; Amod, Zaytoon; Vorster, Adri; Kern, Anwynne (Frontiers in Psychiatry, 2016)
Adolescents with autism and their families experience a significant increase in the number of challenges encountered when leaving the structure of the formal education system. The purpose of this study was to gain an understanding of the factors parents and professionals regard as important in preparing for transition of adolescents with autism spectrum disorder (ASD) to adulthood, vocational and residential arrangements. Semi-structured interviews were conducted with 14 participants (i.e. 7 parents and 7 professionals) who were involved with adolescents with ASD in Johannesburg, South Africa. The findings revealed that there was a need for advocacy on behalf of learners with ASD transitioning into adult working and living environments. The responses of the participants highlighted needs for curriculum transformation from basic literacy skills to development and teaching of functional self-help and daily living skills. The results also indicated lack of planning and the absence of service facilities for adolescents with Autism post-school. There was a general feeling of fear and uncertainty when the participants thought about transition of adolescents with Autism and their future. However, there was also a sense of hope and optimism. Transition of adolescents with Autism into adulthood is a challenging and stressful time for parents and professionals involved in trying to prepare them. With appropriate attention and support structures, individuals with Autism can attain a reasonable quality of life, including residential, employment and social opportunities.